Screening of volcanic cave actinomycetes for antimicrobial activity against Paenibacillus larvae, a honey bee pathogen - Kay S. (2014)
Actinomycete strains isolated from Helmcken Falls cave in Wells Gray Provincial Park, British Columbia were discovered to have antimicrobial activity against Paenibacillus larvae, the causative agent of American foulbrood disease in honeybees. The antimicrobial activity of 119 isolates grown in three fermentation liquid media, namely YMG, AMHU- 4 and V8 juice, at 28°C on an orbital shaker at 250 rpm for 7 days, were tested against P. larvae (ATCC 13537T) using the paper disc agar diffusion method. Of the strains screened, strain E9, grown in V-8 juice medium showed significant antibacterial activity against P. larvae with a maximum activity on day 4 of incubation at pH 7. Chemotaxonomic study and phylogenetic analysis based on 16S rRNA gene sequence revealed that strain E9 is a member of the genus Streptomyces. This is the first report on bioprospecting in volcanic caves of Canada.